จริยธรรมทางการเงินและวินัยทางการคลังของมหาวิทยาลัยทางพระพุทธศาสนา - ทรงสังขาร, จรัสพร (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 1 No 3 (2024): วารสาร มมร ยศสุนทรปริทรรศน์ ปีที่ 1 ฉบับที่ 3 : กันยายน - ธันวาคม 2567, 2024)
Financial ethics and fiscal discipline are critical issues in university management systems, particularly in Buddhist universities, which play a vital role in disseminating Buddhist teachings and fostering sustainable societal development. This article aims to explore the concepts and application of financial ethics and fiscal discipline within the context of Buddhist universities by employing an analytical framework that examines the relationship between Buddhist principles, such as mattanuta and aparihaniyadhamma, and modern financial management practices. The academic essence and intention of this article focus on demonstrating that financial ethics and fiscal discipline aligned with Buddhist principles possess the potential to balance resource allocation for development and maintain the fiscal stability of institutions. Moreover, integrating these principles can promote transparency, accountability, and long-term financial sustainability. However, implementing financial ethics in Buddhist universities faces several challenges, including resource constraints, personnel limitations, and administrative structures. The findings highlight the necessity of developing strategic plans emphasizing collaboration between universities and communities, alongside training programs for personnel to enhance financial management capacity rooted in ethical principles and fiscal discipline. The results of this study provide not only a pathway for the development of Buddhist universities but also serve as a valuable case study for educational institutions worldwide that prioritize ethics and sustainability.